La Nouvelle Alliance d’I. Prigogine et I. Stengers (1979) : mise en récit apologétique de la thermodynamique ou dialogue singulier entre un physicien et une philosophe ? - Emanuel Bertrand (Revue d’Histoire des Sciences Humaines)
In 1979, the physicist Ilya Prigogine and the philosopher Isabelle Stengers published in French a book entitled La Nouvelle Alliance. Métamorphose de la science. Later translated in English, in 1984, as Order out of chaos: Man’s new dialogue with nature, this is an atypical essay, not only combining both history of physics and philosophical reflexions about it, but also using technical mathematical physics developments to strengthen its theses. We will first analyse the nature of the “nouvelle alliance” which the authors are promoting. We shall then focus on the fact that, despite all their explicit efforts, the authors are still stuck within the disciplinary borders they intend to move, or even remove. In a sense, they perpetuate a hierarchical divide between the established disciplines that physics and philosophy represent. Finally, we will try to show how their narrative tends to overestimate the interpretative power of Prigogine’s thermodynamics.